Collisional excitation of CH2 rotational/fine-structure levels by helium. Issue 4 (14th October 2017) - Dagdigian, P. J.; Lique, F.
Abstract: Accurate determination of the abundance of CH2 in interstellar media relies on both radiative and collisional rate coefficients. We investigate here the rotational/fine-structure excitation of CH2 induced by collisions with He. We employ a recoupling technique to generate fine-structure-resolved cross-sections and rate coefficients from close coupling spin-free scattering calculations. The calculations are based on a recent, high-accuracy CH2 –He potential energy surface computed at the coupled clusters level of theory. The collisional cross-section calculations are performed for all fine-structure transitions among the first 22 and 24 energy levels of ortho- and para-CH2, respectively, and for temperatures up to 300 K. As a first application, we simulate the excitation of CH2 in typical molecular clouds. The excitation temperatures of the CH2 lines are found to be small at typical densities of molecular clouds, showing that the non-local thermodynamic equilibrium approach has to be used to analyse interstellar spectra. We also found that the fine-structure lines connected with the 404 − 313 and 505 − 414 rotational transitions show possible maser emissions so that they can be easily seen in emission. These calculations show that CH2 may have to be detected mainly through absorption spectra.